Using Social Media to Engage Communities with Research: Evaluating your Success - Kirsten A. Hecht; Lisa Lundgren; Kathryn A. Stofer; Tyus Williams (EDIS)
This new 5-page publication of the UF/IFAS Department of Agricultural Education and Communication focuses on methods and tools for evaluating the success of your social media engagement. It is part of a series on using social media for engaging with the public about research, titled Using Social Media to Engage Communities with Research. Written by Kirsten Hecht, Lisa Lundgren, Kathryn A. Stofer, and Tyus D. Williams.